Dental Anxiety and Its Possible Effects on Caries Prevalence Among Group of Dental Students In Kathmandu Medical College - Roy, Deepak Kumar; Dixit, Punam Basnet; Ghimire, Siddharth; Roy, Roshan Kumar; Pandey, Aashish; Maharaj, Anuranjan (Journal of Nepalgunj Medical College, 2019)
Introduction: The prevalence of high dental anxiety varies from 2% to 30% worldwide depending on the study population, the methods applied, and the cut-off scores used. There is strong evidence that dental anxiety is associated with dental attendance; it has been reported that individuals with higher dental anxiety tend to visit the dentist irregularly, which in turn may lead to deterioration in oral health. Studies have demonstrated that dental anxiety is associated with poor self-reported and clinically assigned oral health, more decayed and missing teeth, fewer filled teeth and worse periodontal health. Dental students are the future dental doctors who will be dealing with fearful patients in future. Knowing the facts on dental anxiety will have positive impact while treating and dealing such patients.Objectives: The overall objectives of the study were to assess level of anxiety and its possible effect on prevalence of caries among dental students studying at Kathmandu medical college and Dental hospital. Specific: To access the level of anxiety among dental students of different years (from first year to final year) along it was further focused to analyse the level of anxiety among male and female dental students.Methodology: A cross sectional study was conducted to choose a random convenient sample. The data were collected from dental students of first year to final year studying at Kathmandu medical college dental hospital–KMCDH. A structured questionnaire based on modified dental anxiety scale was used to collect the data. Patients were examined for dental caries prevalence using decay, missing and filled teeth (DMFT) index according to World Health Organisation guidelines.Results: The highest MDAS was seen among the younger batches and the mean values for MDAS declined with higher batch of dental students. The mean dental anxiety score for males was 8.9 and 15.5 for females. The difference was statistically significant the most fearful stimulus in dental clinic for both genders was local anesthetic injection, followed by drilling of teeth.Conclusion: Dental anxiety remains a significant problem for many patients of both gender and different age groups of examined students. Dental anxiety has a negative effect on oral health status by increasing the prevalence of decayed teeth. Further studies should be carried out using large random samples before generalizing this conclusion.